2012
DOI: 10.3233/cbm-2012-0242
|View full text |Cite
|
Sign up to set email alerts
|

Hypermethylation of collagen α2 (I) gene (COL1A2) is an independent predictor of survival in head and neck cancer

Abstract: Abstract.Objectives: Collagen production plays a role in the development of tumors from cancer cells. The aim of the present study is to examine the involvement of epigenetic alteration of Collagen α2 (I) (COL1A2) gene expression in cases of head and neck squamous cell carcinoma (HNSCC). Methods: COL1A2 expression was examined in a panel of cell lines using RT-PCR. The methylation status of the COL1A2 promoter was studied using bisulfate sequencing and methylation-specific PCR (MSP). Results: COL1A2 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 35 publications
0
29
1
Order By: Relevance
“…We observed in our results that the expression of COL1A2 was significantly elevated in gastric tumor tissues. In previous research, elevated COL1A2 expression has also been found in many different types of cancers, including breast cancer [22], head and neck cancer [4], and colorectal cancer [23]. We failed to observe the prognostic value of COL1A2 in the current analysis, whereas Misawa et al reported that the COL1A2 gene might serve as an important biomarker in head and neck squamous cell carcinoma [4].…”
Section: +contrasting
confidence: 52%
See 2 more Smart Citations
“…We observed in our results that the expression of COL1A2 was significantly elevated in gastric tumor tissues. In previous research, elevated COL1A2 expression has also been found in many different types of cancers, including breast cancer [22], head and neck cancer [4], and colorectal cancer [23]. We failed to observe the prognostic value of COL1A2 in the current analysis, whereas Misawa et al reported that the COL1A2 gene might serve as an important biomarker in head and neck squamous cell carcinoma [4].…”
Section: +contrasting
confidence: 52%
“…In previous research, elevated COL1A2 expression has also been found in many different types of cancers, including breast cancer [22], head and neck cancer [4], and colorectal cancer [23]. We failed to observe the prognostic value of COL1A2 in the current analysis, whereas Misawa et al reported that the COL1A2 gene might serve as an important biomarker in head and neck squamous cell carcinoma [4]. Controversy regarding the role of COL1A2 in various cancers exists, and we did not identify COL1A2 as a prognostic indicator of gastric cancer in this study.…”
Section: +mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expression levels of COL1A1 and COL1A2 in malignant tumors remain controversial. On one hand, frequent promoter methylation of COL1A1 was detected in renal cell carcinoma and hepatocellular carcinoma [9, 10], and COL1A2 was downregulated in melanoma [11], head and neck cancer [14], and bladder cancer [15]. On the other hand, COL1A1 and COL1A2 mRNA was upregulated in colorectal cancer and medulloblastoma [16, 17].…”
Section: Discussionmentioning
confidence: 99%
“…Endostatin, a collagen XVIII fragment, was shown to inhibit tumor progression by directly affecting the tumor cells, rather than only acting via the endothelial cells to block angiogenesis (21). Furthermore, the hypermethylation of COL1A2 was found to be an independent predictor of survival in patients with head and neck cancer (22).…”
Section: Col22a1 Col23a1mentioning
confidence: 99%